The JESSICA Initiative: An Instrument for Urban Sustainable Development. Examples of Urban Regeneration in Silesia (Poland) and Central Moravia (Czech Republic) - Tarnowska, Katarzyna; Rosiek, Janusz (Comparative Economic Research. Central and Eastern Europe, 2015)
This article presents the practical possibilities associated with implementation of the JESSICA initiative in selected regions of Poland and the Czech Republic. i.e. in Silesia (Poland) and Central Moravia (Czech Republic). The post-socialist nature of these regions was determinative of their backwardness in terms of socio-economic development, as well as available infrastructure. Nonetheless these regions are different to a large extent, because Silesia is a typical post-industrial area, where the mining industry has been in operation for many years. After significant limitation of the scale of its economic operations, many areas and objects remain unused. They can be revitalized and then used to contribute to more sustainable socio-economic development of the region. In turn, Central Moravia represents a geographical area which has been adversely affected by the effects of the ongoing economic crisis. To some extent, Silesia suffers from similar problems as Central Moravia, but it also encounters some specific difficulties arising from its post-industrial character. For this reason, there was a necessity to properly identify opportunities to support projects financed from the JESSICA initiative in the analyzed regions, as well as to adapt the scope of these projects to the specific socio-economic conditions in the regions under investigation.